Analysis of eating disorders developed after bariatric surgery (Research, Society and Development, 2024)
The treatment of obesity is linked to reducing the risks of associated comorbidities, and also relies on psychological aspects, whether there is motivation and whether the patient is willing to try to change their lifestyle. Bariatric surgery, also known as stomach reduction. Objective: to elucidate the psychological impacts generated in patients undergoing this procedure, as well as the care needed before and after surgery. Methodology: the study was carried out through a bibliographic literature review. Scientific documents and official documents from National Health Organizations were used and works published in the last ten years (2014-2024) were selected, with the exception of two articles, one from 2004 and the other from 1984, which were relevant to the study, in Portuguese languages and English. The databases searched were SCIELO, PUBMED, VHL, MEDLINE and SBCBM. Discussion: emphasize the importance of long-term follow-up after bariatric surgery, highlighting the need to maintain support and ongoing treatment to help patients adopt a new post-surgery lifestyle. Final considerations: There is a relationship between weight regain and the occurrence of eating disorders in the bariatric population, even with a positive response in anxiety and depression, reducing the incidence of these disorders after surgery, emotional and eating issues were cited as main predictors of weight regain.